A self-assembled hydrophobic coating coated sodium nickel iron manganese oxide positive electrode material and preparation method thereof and sodium ion battery
Through self-assembly hydrophobic coating technology, a uniform coating layer is formed on the surface of O3 type sodium ferromanganate positive electrode material, which solves the problem of poor air stability of the material and achieves high voltage cycling stability and excellent capacity retention.
Patent Information
- Application Number
- CN202411473108.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The air stability of the O3-type layered oxide positive electrode material is poor, resulting in capacity loss and difficulty in producing electrodes. The existing coating methods lead to uneven material coating and limited improvement in air stability.
By using self-assembled hydrophobic coating technology, the liquid phase of the alkyl phosphate ester is self-adsorbed on the surface of the O3 type sodium ni-ferromanganate positive electrode material to form a uniform coating layer. After sintering through an inert atmosphere, the alkyl phosphate ester reacts with the residual sodium salt on the surface of the sodium ni-ferromanganate positive electrode material to form a stable alkyl sodium phosphate coating.
The excellent air stability and high voltage cycle stability of the sodium nickel ferromanganate cathode material have been achieved. The 1C capacity retention rate of the material within the 2-4.1V voltage range reaches 95%, and the capacity retention rate of the one-day storage in humid air is 99.8%.
Smart Images

Figure CN119029189B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and mainly relates to a self-assembled hydrophobic coating-coated sodium nickel iron manganate positive electrode material, a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the growing demand for electronic devices and electric mobility tools, lithium-ion batteries have been widely used as important energy storage devices. However, due to the shortage, high cost and uneven distribution of lithium resources, and the abundance, easy access and low cost of sodium resources, sodium-ion battery technology has developed rapidly, and the industrialization process in the fields of energy storage and small power is also advancing rapidly. The positive electrode material is the core component of the battery. At present, the positive electrode materials of sodium-ion batteries can be divided into layered oxides, Prussian blue and polyanions. Among them, the layered transition metal oxide positive electrode material has a high energy density and compaction density, and has a similar synthesis route to lithium battery ternary materials. It is considered to be a more ideal positive electrode material for sodium-ion batteries.
[0003] O3-type layered oxides for sodium-ion batteries have the advantages of high initial sodium content and high capacity. However, O3-type layered oxides have poor air stability, leading to capacity loss and difficulties in electrode manufacturing. A large number of studies have shown that surface coating is one of the effective ways to solve the poor air stability of materials. Existing coating materials mainly include metal oxides, fluorides, and polyanion materials. However, due to the problem of coating method, the material coating layer is uneven, the material is still in contact with the air, and the improvement in air stability is limited. Summary of the invention
[0004] In order to overcome the problems in the prior art, the present invention provides a self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material and a preparation method thereof, and the prepared sodium ion battery positive electrode material has excellent air stability and high voltage cycle stability. The hydrophobic alkyl phosphate liquid phase is self-adsorbed on the surface of the O3 type sodium nickel iron manganate positive electrode material to form a uniform coating layer. After sintering in an inert atmosphere, the alkyl phosphate reacts with the sodium salt remaining on the surface of the sodium nickel iron manganate positive electrode material to generate an alkyl sodium phosphate coating that is uniformly and stably coated and chemically bonded to the positive electrode material. The uniform carbon chain-containing sodium phosphate coating layer protects the material from air corrosion while ensuring the sodium ion deintercalation ability in the lattice. At the same time, the coating layer can reduce the side reactions between the material and the electrolyte and ensure the high voltage cycle stability of the material.
[0005] In an embodiment of the present invention, the present invention provides a self-assembled hydrophobic coating coated with sodium nickel iron manganate positive electrode material, the chemical formula of the self-assembled hydrophobic coating coated with sodium nickel iron manganate positive electrode material is: AP-Na@[Na 1-x M x / n ](Ni aFe b Mn c ) 1-y N y O2, wherein AP-Na is an alkyl sodium phosphate coating, M is one or two of Li, K, and Ca metal ions, N is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, and W metal ions, n is the valence state of the M metal ion, 0<x, y≤0.1, and the values of a, b, and c depend on the charge balance.
[0006] As an optional implementation, the self-assembled hydrophobic coating has a thickness of 1-10 nm.
[0007] As an optional embodiment, the alkyl group in the sodium alkyl phosphate coating is one or more of dodecyl, tetradecyl, hexadecyl or octadecyl.
[0008] Based on the same inventive concept, the present invention proposes a method for preparing the above-mentioned self-assembled hydrophobic coating coated sodium nickel iron manganese oxide positive electrode material, comprising the following steps:
[0009] S1, preparing a nickel-iron-manganese hydroxide precursor by a coprecipitation method from a nickel-iron-manganese source, then mixing the nickel-iron-manganese hydroxide precursor with a sodium source, a doping source containing M, and a doping source containing N by ball milling, and then sintering the mixture in an oxidizing atmosphere to obtain a sodium nickel-iron-manganese oxide positive electrode material;
[0010] S2, dissolving an alkyl phosphate in an organic solvent to obtain a solution C1, uniformly dispersing the sodium nickel iron manganese oxide positive electrode material in anhydrous ethanol to obtain a suspension C2, and then dropping the solution C1 into the suspension C2, heating in a water bath with stirring, evaporating to dryness, and then grinding to obtain a coating precursor;
[0011] S3, calcining the coating-coated precursor under an inert atmosphere to obtain a self-assembled hydrophobic coating-coated sodium nickel iron manganese oxide positive electrode material.
[0012] As an optional embodiment, the doping source containing M is any one or more of a lithium source, a potassium source or a calcium source; the doping source containing N is one or more of Mg(OH)2, Cu(OH)2, MgO, Al2O3, ZnO, TiO2, ZrO2, Nb2O5, WO3.
[0013] As an optional embodiment, the alkyl phosphate is one or more of dodecyl phosphate, tetradecyl phosphate, hexadecyl phosphate, and octadecyl phosphate, and the mass ratio of the alkyl phosphate to the sodium nickel iron manganese oxide positive electrode material is 0.005~0.05:1.
[0014] As an optional embodiment, the molar ratio of the metal element content in the hydroxide precursor, the sodium content in the sodium source, the metal element in the doping source containing M and the metal element in the doping source containing N is 1:(0.9-1.05):(0.001-0.1):(0.001-0.1).
[0015] As an optional embodiment, the sintering process in step S1 includes pre-calcination and re-calcination, the pre-calcination is to increase the temperature from room temperature to 300-600°C at a heating rate of 1-10°C / min, and pre-calcination for 4-10h; the re-calcination is to increase the temperature to 800-950°C at a heating rate of 1-10°C / min, and calcination for 6-15h.
[0016] As an optional implementation, the water bath temperature in step S2 is 50-80°C.
[0017] As an optional implementation, the calcination process in step S3 is to heat the temperature from room temperature to 200-500° C. at a heating rate of 1-10° C. / min for 1-10 h.
[0018] Based on the same inventive concept, an embodiment of the present invention further provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery comprises the above-mentioned self-assembled hydrophobic coating-coated sodium nickel iron manganese oxide positive electrode material.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The self-assembled hydrophobic coating of the present invention is coated with the sodium nickel iron manganese oxide positive electrode material, wherein the alkyl sodium phosphate coating includes a sodium phosphate structure bonded to the positive electrode material and a hydrophobic alkyl structure of the outer layer. The sodium phosphate structure is a fast ion conductor that can accelerate ion transfer, avoid the problem that the hydrophobic layer becomes an obstacle to ion diffusion, and improve the air stability of the material while ensuring the ion diffusion capacity of the material. Therefore, the positive electrode material of the present invention has excellent electrical properties and cycle stability. The uniform carbon chain-containing sodium phosphate coating layer can reduce the side reaction of the material and the electrolyte under high voltage while protecting the material from air corrosion, thereby ensuring the cycle stability of the material. When applied to sodium ion batteries, in the voltage range of 2-4.1V, the material has a 1C capacity retention rate of 95%, and a capacity retention rate of 99.8% after one day of storage in humid air.
[0021] (2) The present invention The present invention forms a uniform coating layer by adsorbing alkyl phosphate on the surface of O3 type sodium nickel iron manganate positive electrode material through liquid phase self-assembly, and after sintering in an inert atmosphere, the alkyl phosphate reacts with the sodium salt remaining on the surface of the sodium nickel iron manganate positive electrode material to form a sodium phosphate coating layer containing a carbon chain. Specifically, it includes the steps of water bath heating self-assembly, grinding and calcination. In the above process, the alkyl phosphate is used as the coating material, which has a hydrophilic structure phosphate and a hydrophobic structure alkyl. On the one hand, it can self-assemble in the liquid phase to form a uniform coating structure. On the other hand, the coating material has a certain reactivity and reacts chemically with the active structure on the surface of the positive electrode material under certain conditions to form a uniform alkyl sodium phosphate coating with a stable coating layer. Secondly, the reaction process of the present invention is carried out in an organic solvent system, and self-assembly is carried out by low-temperature water bath heating. The organic solvent does not react with the positive electrode material. The alkyl phosphate material is not lost or decomposed during the preparation process. First, a uniform and stable coating layer is formed by self-assembly, and then sintering in an inert atmosphere is performed to form a sodium phosphate coating layer containing a carbon chain. The raw materials of the preparation method are easily available, the synthesis method is relatively simple and easy to operate, the synthesis cycle is short, the prepared coating material has excellent recycling performance, good economy, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 XRD spectra of the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material prepared in Example 1 of the present invention and the pure phase sodium nickel iron manganate positive electrode material prepared in Comparative Example 1;
[0024] Figure 2 The SEM images of the self-assembled hydrophobic coating coated sodium nickel iron manganese oxide positive electrode material prepared in Example 1 of the present invention, wherein (a, b) are the materials before sintering, and (c, d) are the materials after sintering;
[0025] Figure 3 TEM images of the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material prepared in Example 1 of the present invention and the pure phase sodium nickel iron manganate positive electrode material prepared in Comparative Example 1; (a) is Example 1, and (b) is Comparative Example 1;
[0026] Figure 4The cycling performance of the sodium nickel iron manganate positive electrode material coated with the self-assembled hydrophobic coating prepared in Example 1 of the present invention and the pure phase sodium nickel iron manganate positive electrode material prepared in Comparative Example 1 at a current rate of 1C in the voltage range of 2-4.1V;
[0027] Figure 5 The first charge and discharge curves at a current rate of 0.1C in the voltage range of 2-4.1V after the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material prepared in Example 1 of the present invention and the pure phase sodium nickel iron manganate positive electrode material prepared in Comparative Example 1 were placed in a 60% humidity environment for 24 hours; wherein (a) is Example 1, and (b) is Comparative Example 1. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] The chemical formula of the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material of the present invention is AP-Na@[Na 1-x M x / n ](Ni a Fe b Mn c ) 1-y N y O2, where AP-Na is an alkyl sodium phosphate coating, M is one or two of Li, K, and Ca metal ions, N is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, and W metal ions, n is the valence state of the M metal ion, 0<x, y≤0.1, and the values of a, b, and c depend on the charge balance. The thickness of the self-assembled hydrophobic coating is 1~10nm. Too thick will hinder the transmission of sodium ions, reduce the proportion of active substances, and affect the discharge capacity of the material. The alkyl group in the alkyl sodium phosphate coating is one or more of dodecyl, tetradecyl, hexadecyl, or octadecyl. The alkyl sodium phosphate hydrophobic coating is uniformly coated on the surface of the sodium nickel iron manganese oxide positive electrode material, which can protect the positive electrode material from air corrosion, and at the same time reduce the side reaction between the positive electrode material and the electrolyte, ensuring the high voltage cycle stability of the material.
[0032] The method for preparing the above-mentioned self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material comprises the following steps:
[0033] S1. Prepare a nickel-iron-manganese hydroxide precursor by coprecipitation from a nickel-iron-manganese source, then ball-mill and mix the nickel-iron-manganese hydroxide precursor with a sodium source, a doping source containing M, and a doping source containing N, and then sinter under an oxidizing atmosphere to obtain a sodium nickel-iron-manganese acid positive electrode material. In this process, the nickel-iron-manganese source is a soluble nickel salt, an iron salt, and a manganese salt. The coprecipitation method refers to adding a precipitant and a complexing agent to react to generate a hydroxide, wherein the precipitant is a NaOH solution and the complexing agent is NH3·H2O. The doping source containing M is a lithium source, a potassium source, or a calcium source, and the lithium source and the potassium source are one or more of Li / KOH, Li / K2CO3, Li / K2C2O4, or Li / KCl, and the calcium source is one or more of CaO, CaCO3, Ca(HCO3)2, or Ca(OH)2. The metal oxides or metal hydroxides containing N are Mg(OH)2, Cu(OH)2, MgO, Al2O3, ZnO, TiO2, ZrO2, Nb2O5, and WO3. The molar ratio of the metal element content in the hydroxide precursor, the sodium content in the sodium source, the metal element in the doping source containing M, and the metal element in the doping source containing N is 1: (0.9-1.05): (0.001-0.1): (0.001-0.1), wherein the doped M and N are both inactive elements, which do not participate in the reaction during the charge and discharge process, and their function is to improve the cycle stability of the material, so the content cannot be too high; excessive doping will lead to a decrease in the proportion of active metal elements and a decrease in the material capacity, and excessive doping will lead to the problem of being unable to be doped, forming impurities. The sintering process includes pre-calcination and re-calcination. The pre-calcination is to heat the temperature from room temperature to 300-600°C at a heating rate of 1-10°C / min for 4-10 hours; the re-calcination is to heat the temperature to 800-950°C at a heating rate of 1-10°C / min for 6-15 hours. During the sintering process, water in the precursor is first removed at 300-600°C, and then high-temperature calcination is performed at 800-950°C to obtain a sodium nickel iron manganese oxide positive electrode material in which metal M is doped in a sodium layer and metal N is doped in a transition metal layer.
[0034] S2, dissolving the alkyl phosphate in an organic solvent (the organic solvent is a polar organic solvent, preferably tetrahydrofuran) to obtain solution C1, uniformly dispersing the sodium nickel iron manganate cathode material in anhydrous ethanol to obtain suspension C2, and then dropping the solution C1 into the suspension C2, heating the ester in a water bath at 50-80°C, stirring and evaporating to dryness, and then grinding to obtain a coating-coated precursor. The purpose of water bath heating is to evaporate and remove organic matter to ensure that the alkyl phosphate is evenly distributed on the surface of the cathode material. If the water bath temperature is too high, segregation may occur if the evaporation is too fast; if the water bath temperature is too low, the longer the exposure time of the cathode material, the performance may decay. In this process, the mass ratio of alkyl phosphate to sodium nickel iron manganate cathode material is 0.005-0.05:1 to ensure that the alkyl phosphate can be self-assembled and coated on the surface of the cathode material. Too high an addition amount will result in too thick a coating, affecting the sodium ion transmission, and too low an addition amount will result in an inability to uniformly coat, and the improvement in air stability is limited. In this process, an organic solvent system is used, and low-temperature water bath heating is adopted for self-assembly. The organic solvent does not react with the positive electrode material, and the alkyl phosphate material is not lost or decomposed in the process, and self-assembles to form a uniform and stable coating layer.
[0035] S3, the coating-coated precursor is calcined under an inert atmosphere, specifically at a heating rate of 1-10 ° C / min from room temperature to 200-500 ° C, and calcined for 1-10h to obtain a self-assembled hydrophobic coating coated with sodium nickel iron manganate positive electrode material. In this process, the sodium salt remaining on the surface of sodium nickel iron manganate reacts with the alkyl phosphate to form an alkyl sodium phosphate coating layer, reducing the influence of the sodium ion diffusion resistance of the coating layer. In this process, the calcination temperature is controlled so that the alkyl phosphate reacts with the sodium salt remaining on the surface of the positive electrode material to form an alkyl sodium phosphate coating, wherein the sodium phosphate structure is a fast ion conductor, which can accelerate ion transfer, avoid the problem of the hydrophobic layer becoming an obstacle to ion diffusion, and improve the air stability of the material while ensuring the ion diffusion capacity of the material.
[0036] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0037] In the coprecipitation reaction process of the following embodiment of the present invention, the nickel, iron and manganese salts are NiSO4·7H2O, FeSO4·7H2O and MnSO4·H2O, and the precipitant is a precipitant with a concentration of 4 mol / L -1 NaOH solution, the complexing agent is 20wt% NH3·H2O, the coprecipitation reaction temperature is 45°C, and the system pH is controlled at 11. It should be understood that the above nickel-iron-manganese salt can also use other soluble salts, and the concentrations of the precipitant and the complexing agent can also be adaptively adjusted.
[0038] Example 1
[0039] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0040] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0041] (2) Dissolve 0.05 g of octadecyl phosphate in 5 mL of tetrahydrofuran solution. Disperse 5 g of sodium nickel iron manganate positive electrode material in 45 mL of anhydrous ethanol according to the mass ratio of octadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.001:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 70 ° C and evaporate to dryness. After grinding, heat the powder to 400 ° C at 5 ° C / min in an argon atmosphere and calcine for 2 h to obtain 0.1%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0042] Example 2
[0043] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0044] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0045] (2) Dissolve 0.01 g of octadecyl phosphate in 5 mL of tetrahydrofuran solution. Disperse 5 g of sodium nickel iron manganate positive electrode material in 45 mL of anhydrous ethanol according to the mass ratio of octadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.002:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 70 ° C and evaporate to dryness. After grinding, heat the powder to 400 ° C at 5 ° C / min in an argon atmosphere and calcine for 2 h to obtain 0.2%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0046] Example 3
[0047] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0048] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0049] (2) Dissolve 0.01 g of octadecyl phosphate in 5 mL of tetrahydrofuran solution. Disperse 5 g of sodium nickel iron manganate positive electrode material in 45 mL of anhydrous ethanol according to the mass ratio of octadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.002:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 70 ° C and evaporate to dryness. After grinding, heat the powder to 500 ° C at 5 ° C / min in an argon atmosphere and calcine for 6 hours to obtain 0.2%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0050] Example 4
[0051] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0052] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0053] (2) Dissolve 0.01 g of hexadecyl phosphate in 5 mL of tetrahydrofuran solution. Disperse 5 g of sodium nickel iron manganate positive electrode material in 45 mL of anhydrous ethanol according to the mass ratio of hexadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.002:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 70 ° C and evaporate to dryness. After grinding, heat the powder to 400 ° C at 5 ° C / min in an argon atmosphere and calcine for 2 h to obtain 0.2%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0054] Example 5
[0055] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0056] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0057] (2) Dissolve 0.01 g of hexadecyl phosphate in 5 mL of tetrahydrofuran solution. Disperse 5 g of sodium nickel iron manganate positive electrode material in 45 mL of anhydrous ethanol according to the mass ratio of hexadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.002:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 60°C and evaporate to dryness. After grinding, heat the powder to 400°C at 5°C / min in an argon atmosphere and calcine for 2 hours to obtain 0.2%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0058] Comparative Example 1
[0059] A method for preparing a pure phase sodium nickel iron manganate ternary positive electrode material comprises the following steps:
[0060] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0061] Comparative Example 2
[0062] A method for preparing a positive electrode material coated with a self-assembled hydrophobic coating of sodium nickel iron manganate comprises the following steps:
[0063] (1) Ni was prepared by coprecipitation with a molar ratio of Ni:Fe:Mn of 1:1:1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, take 0.99 mol Ni1 / 3 Fe 1 / 3 Mn 1 / 3 The (OH)2 precursor was fully ball-milled with 0.495 mol Na2CO3, 0.005 mol CaO and 0.01 mol TiO2, heated to 500°C at 5°C / min in an oxygen atmosphere, pre-sintered for 4 h, and then heated to 870°C and sintered for 12 h to obtain a product with the chemical formula [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 Sodium nickel iron manganese oxide positive electrode active material for O2.
[0064] (2) Dissolve 0.75g of octadecyl phosphate in 5mL of tetrahydrofuran solution. Disperse 5g of sodium nickel iron manganate positive electrode material in 45mL of anhydrous ethanol according to the mass ratio of octadecyl phosphate to sodium nickel iron manganate positive electrode material of 0.015:1. Add the tetrahydrofuran solution of octadecyl phosphate dropwise into the ethanol dispersion of sodium nickel iron manganate material to obtain a mixed suspension. Stir the mixed suspension in a water bath at 60°C and evaporate to dryness. After grinding, heat the powder to 400°C at 5°C / min in an argon atmosphere and calcine for 2h to obtain 15%wt AP-Na@[Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material.
[0065] Structural analysis and performance testing
[0066] The positive electrode materials obtained in the above examples and comparative examples were subjected to XRD analysis, scanning electron microscopy analysis and transmission electron microscopy analysis. Taking Example 1 and Comparative Example 1 as examples, the specific results are shown in Figure 1 , 2 , as shown in Figure 3.
[0067] Figure 1 The XRD spectra obtained in Example 1 and Comparative Example 1 show that the material has a good crystal structure and all peak shapes are consistent with the standard card, proving that [Na 0.99 Ca 0.005 ][Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ] 0.99 Ti 0.01 O2 positive electrode material, and it is shown that the hydrophobic layer coating will not affect the crystal structure of the material. Figure 2The SEM images of the positive electrode material prepared in Example 1 before and after sintering, where Figures (a, b) are SEM images of the hydrophobic layer-coated positive electrode material before sintering. The sample surface is rough and covered with a large number of nanoparticles. The surface hydrophobic layer successfully adheres to the surface of the sodium nickel iron manganese oxide positive electrode material. Figures (c, d) are SEM images of the positive electrode material after sintering. From the images, it can be seen that the nanoparticles on the surface of the material disappear, and a uniform coating layer is formed on the surface of the material. Figure 3 TEM images of the positive electrode materials prepared in Example 1 and Comparative Example 1 show that Figure 3 (a) There is an obvious coating layer on the surface of the sodium nickel iron manganese oxide material, with a thickness of about 3~5nm, which further proves that the surface of the material is successfully coated with a hydrophobic layer; Figure 3 (b) The surface of the pure phase sodium nickel iron manganese oxide material is smooth and has no obvious coating layer.
[0068] Electrical performance test:
[0069] The positive electrode materials obtained in the above embodiments and comparative examples are used for battery assembly, and the steps are as follows: weigh 0.2000g of the above positive electrode material, add 0.0250g of conductive carbon black as a conductive agent and 0.0250g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply it on aluminum foil to make a positive electrode sheet, use a metal sodium sheet as the negative electrode in a vacuum glove box, the battery separator is a WhatmanGF / D glass fiber separator, and the electrolyte is 1mol / L NaClO4 (EC:DMC=1:1 (volume ratio) +5%FEC), and assemble into a CR2025 button battery. The electrochemical performance test is carried out in the range of 2-4.1V, and the capacity retention rate after 100 cycles at a current rate of 1C is measured. In addition, the material is tested for air stability, and the electrical performance test is carried out after being placed in an environment with 60% air humidity for 24 hours, and the capacity retention rate of the material after placement is measured compared with the fresh sample. The results are shown in Tables 1 and Figure 4 , 5 shown.
[0070] Table 1 Electrical performance test results
[0071]
[0072] It can be seen from the battery performance tests of the above embodiments and comparative examples that, compared with the uncoated material, the self-assembled hydrophobic coating coated sodium nickel iron manganate cathode material exhibits better air stability and high-voltage cycle stability. The self-assembled hydrophobic coating can effectively isolate the air, while reducing the contact between the sodium nickel iron manganate cathode material and the electrolyte, reducing the electrode interface side reactions under high voltage, and improving the high-voltage cycle stability. When the coating amount is too high, the coating thickness increases, resulting in a decrease in the sodium ion diffusion kinetics during the sample charge and discharge process, and an increase in the polarization of the electrochemical reaction, which also results in a decrease in the electrochemical performance of the sample.
[0073] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A self-assembled hydrophobic coating coated with sodium nickel iron manganate positive electrode material, characterized in that: The chemical formula of the self-assembled hydrophobic coating coated with sodium nickel iron manganese oxide positive electrode material is: AP-Na@[Na 1-x M x / n ](Ni a Fe b Mn c ) 1-y N y O2, wherein AP-Na is an alkyl sodium phosphate coating, M is one or two of Li, K, and Ca metal ions, N is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, and W metal ions, n is the valence state of the M metal ion, 0<x, y≤0.1, and the values of a, b, and c depend on the charge balance; The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material comprises the following steps: S1, preparing a nickel-iron-manganese hydroxide precursor by a coprecipitation method from a nickel-iron-manganese source, then mixing the nickel-iron-manganese hydroxide precursor with a sodium source, a doping source containing M, and a doping source containing N by ball milling, and then sintering the mixture in an oxidizing atmosphere to obtain a sodium nickel-iron-manganese oxide positive electrode material; S2, dissolving an alkyl phosphate in an organic solvent to obtain a solution C1, uniformly dispersing the sodium nickel iron manganese oxide cathode material in anhydrous ethanol to obtain a suspension C2, and then dropping the solution C1 into the suspension C2, heating in a water bath with stirring, evaporating to dryness, and then grinding to obtain a coating precursor; the alkyl phosphate is one or more of dodecyl phosphate, tetradecyl phosphate, hexadecyl phosphate, and octadecyl phosphate; S3, calcining the coating-coated precursor under an inert atmosphere to obtain a self-assembled hydrophobic coating-coated sodium nickel iron manganese oxide positive electrode material; The calcination process in step S3 is to heat the temperature from room temperature to 200-500° C. at a heating rate of 1-10° C. / min for 1-10 hours.
2. The self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to claim 1, characterized in that: The thickness of the self-assembled hydrophobic coating is 1-10 nm.
3. The method for preparing a self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, preparing a nickel-iron-manganese hydroxide precursor by a coprecipitation method from a nickel-iron-manganese source, then mixing the nickel-iron-manganese hydroxide precursor with a sodium source, a doping source containing M, and a doping source containing N by ball milling, and then sintering the mixture in an oxidizing atmosphere to obtain a sodium nickel-iron-manganese oxide positive electrode material; S2, dissolving an alkyl phosphate in an organic solvent to obtain a solution C1, uniformly dispersing the sodium nickel iron manganese oxide cathode material in anhydrous ethanol to obtain a suspension C2, and then dropping the solution C1 into the suspension C2, heating in a water bath with stirring, evaporating to dryness, and then grinding to obtain a coating precursor; the alkyl phosphate is one or more of dodecyl phosphate, tetradecyl phosphate, hexadecyl phosphate, and octadecyl phosphate; S3, calcining the coating-coated precursor under an inert atmosphere to obtain a self-assembled hydrophobic coating-coated sodium nickel iron manganese oxide positive electrode material; The calcination process in step S3 is to heat the temperature from room temperature to 200-500° C. at a heating rate of 1-10° C. / min for 1-10 hours.
4. The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganese oxide positive electrode material according to claim 3, characterized in that: The doping source containing M is any one or more of a lithium source, a potassium source or a calcium source; the doping source containing N is any one or more of Mg(OH)2, Cu(OH)2, MgO, Al2O3, ZnO, TiO2, ZrO2, Nb2O5, WO3.
5. The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to claim 3, characterized in that: The mass ratio of the alkyl phosphate to the sodium nickel iron manganese oxide positive electrode material is 0.005-0.05:
1.
6. The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to claim 3, characterized in that: The molar ratio of the metal element content in the hydroxide precursor, the sodium content in the sodium source, the metal element in the doping source containing M and the metal element in the doping source containing N is 1:(0.9-1.05):(0.001-0.1):(0.001-0.1).
7. The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to claim 3, characterized in that: The sintering process in step S1 includes pre-calcination and re-calcination. The pre-calcination is to increase the temperature from room temperature to 300-600°C at a heating rate of 1-10°C / min for 4-10 hours; the re-calcination is to increase the temperature to 800-950°C at a heating rate of 1-10°C / min for 6-15 hours.
8. The method for preparing the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to claim 3, characterized in that: The water bath temperature in step S2 is 50-80°C.
9. A sodium ion battery, characterized in that: The positive electrode material in the sodium ion battery comprises the self-assembled hydrophobic coating coated sodium nickel iron manganate positive electrode material according to any one of claims 1 to 2.
Citation Information
Patent Citations
Surface-modified sodium ion positive electrode material and preparation method and application thereof
CN117497724A
Double-site metal ion doped nickel iron sodium manganate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN118315567A